A new species of the palmatisect Anthurium sect. Dactylophyllium (Araceae) from the Atlantic Forest of northern littoral of Bahia, Brazil - Popovkin, Alex V.; Coelho, Marcus A. Nadruz (Phytotaxa, 2025)
A new species of Anthurium sect. Dactylophyllium, A. zalesskii, from the Atlantic Forest of northern littoral of Bahia, Brazil, is here described and illustrated. A distribution map, an updated key to closely related species in the section, and an IUCN conservation ranking are provided.